2018
DOI: 10.1159/000494362
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prestenting on Outcomes of Flexible Ureteroscopy for Upper Urinary Urolithiasis: A Historical Control Study

Abstract: Objectives: The aim of this study is to explore the efficacy and safety of flexible ureteroscopy (fURS) with prestenting (PS) for patients and a newly starting department. Method: The data of patients who underwent fURS for calculi with nonprestenting (NPS) after a clinical practice change was compared with PS patients before. Result: In all, 199 patients met the inclusion criteria. There was no significant difference for both groups in basic demography except that the NPS group included more proximal ureteral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…In our review, Lumma et al found that pre-stenting actually increased the length of the operation by 4 min yet made no difference to the complication rate [14]. Chen et al also found the operative time to be shorter in patients who were pre-stented, on average by 15 min, yet no significant difference in complications [11].…”
Section: Pre-stentingmentioning
confidence: 55%
See 2 more Smart Citations
“…In our review, Lumma et al found that pre-stenting actually increased the length of the operation by 4 min yet made no difference to the complication rate [14]. Chen et al also found the operative time to be shorter in patients who were pre-stented, on average by 15 min, yet no significant difference in complications [11].…”
Section: Pre-stentingmentioning
confidence: 55%
“…Many studies have looked into the role of pre-stenting before URS [11,14]. Stents are most commonly placed if the patient has a compromised renal function, intractable pain, or obstructed infected kidneys; however, some institutions have routinely pre-stented patients prior to URS.…”
Section: Pre-stentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 7 studies including 3,145 patients (PS 1,408; NPS 1,737) were included in this article (Fig. 1) [8][9][10][11][12][13][14]. Table 1 shows the basic characteristics and quality assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies including 2,888 patients (PS 1,254; NPS 1,634) that met the inclusion criteria reported age and gender [8][9][10][12][13][14]. The PS group was found to be associated with older age (WMD 0.91 year, 95% CI 0.72-1.09; p < 0.001) and more male patients (OR 1.34, 95% CI 1.14-1.56; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%